Fluxo de carbono orgânico dissolvido e de nitrato em águas superficiais de duas microbacias da bacia do Rio das Mortes - Santos, Tulio Gonçalves dos (2016)
The present study was carried out in Campo Verde - MT to evaluate the anthropic interference on dissolved organic carbon (DOC) and nitrate (NO3) flows in the surface waters of two mini watersheds. Water samples were collected in two mini watersheds with different soil use (regenerated savanna and an agricultural area) from January 2014 to April 2015. In the rainy season, the samples were collected every 15 days and in the dry period every month. The composite samples were collected by an automatic sampler in the stream. The water flow monitoring was performed with a sensor that measured the hydraulic load on the sill of the triangular spillway installed in each of the mini watershed. Three rain gauges were also installed in each of the mini watersheds to quantify the mean precipitation. The DOC and NO3 contents were analyzed in a UV-Vis spectrophotometer. The flow was estimated with the values of flow and concentrations of DOC and NO3. The mini watershed under cerrado has a higher average flow than the agricultural mini watershed. The increment in the values of specific flow in the days with rainfall is greater in the mini watershed under cerrado. The nitrate concentrations in the two mini watersheds are the same for rainy and dry days. The mini watershed under cerrado has the highest concentrations of dissolved organic carbon, regardless of rainfall. In both watersheds there is a significant increase in the concentration of nitrate and organic carbon dissolved in rainy days. The flows of dissolved organic carbon and nitrate are higher in the Cerrado microbasin, independent of the occurrence of rainfall.